2021
DOI: 10.3389/fphar.2021.749429
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship of Novel Second-Generation Synthetic Cathinones: Mechanism of Action, Locomotion, Reward, and Immediate-Early Genes

Abstract: Several new synthetic cathinones, which mimic the effect of classical psychostimulants such as cocaine or MDMA, have appeared in the global illicit drug market in the last decades. In fact, the illicit drug market is continually evolving by constantly adding small modifications to the common chemical structure of synthetic cathinones. Thus, the aim of this study was to investigate the in vitro and in vivo structure–activity relationship (SAR) of six novel synthetic cathinones currently popular as recreational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 73 publications
1
29
0
Order By: Relevance
“…SAR studies suggest that a more bulky and lipophilic substitution on the amino group promotes increased potency of dopamine reuptake inhibition which translates into strong stimulant effects and large rewarding properties. However, this is not a linear relationship: while the change from an N -methyl to an N -ethyl chain increases potency, substituting the pyrrolidine ring with a larger piperidine ring or with an N,N -diethyl substituent decreases potency [ 140 , 180 , 181 ]. Hence, it is likely that N -butyl analogs have fewer stimulatory properties than their N -ethyl counterparts, but this needs to be confirmed in further studies.…”
Section: Pharmacology and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…SAR studies suggest that a more bulky and lipophilic substitution on the amino group promotes increased potency of dopamine reuptake inhibition which translates into strong stimulant effects and large rewarding properties. However, this is not a linear relationship: while the change from an N -methyl to an N -ethyl chain increases potency, substituting the pyrrolidine ring with a larger piperidine ring or with an N,N -diethyl substituent decreases potency [ 140 , 180 , 181 ]. Hence, it is likely that N -butyl analogs have fewer stimulatory properties than their N -ethyl counterparts, but this needs to be confirmed in further studies.…”
Section: Pharmacology and Toxicitymentioning
confidence: 99%
“…In addition, repeated administration of ephylone caused anxiolytic-like and depressive-like effects and aggressiveness in rats [138,139]. Studies in rodents suggest that ephylone has a high addictive potential [137,[139][140][141]. Additionally, studies in zebrafish showed its neurotoxicity, cardiotoxicity and developmental toxicity [142].…”
Section: N-ethylhexedrone Ephylone and Eutylonementioning
confidence: 99%
“…The uptake inhibition assay was performed as described by [14,61], with minor modifications. Prior to starting the uptake inhibition experiment, the media was aspirated from the cell culture in the 96-well plates and immediately replaced with 200 µL of Krebs-HEPES-Buffer (KHB; 10 mM HEPES, 120 mM NaCl, 3 mM KCl, 2 mM CaCl 2 •2H 2 O, 2 mM MgCl 2 •6H 2 O supplemented with 20 mM D-glucose; pH 7.3).…”
Section: Uptake Inhibition Assaysmentioning
confidence: 99%
“…The apparatus that is used for this test consists of two compartments, with differences in tactile and visual cues, communicated by a central corridor. Conditioned place preference (CPP) was performed as described by [61]. Briefly, CPP was performed in three phases: preconditioning test and conditioning and post-conditioning test.…”
Section: Conditioned Place Preference (Cpp)mentioning
confidence: 99%
“…In this line, specific changes in the cathinone structure have been reported to change the mode of action on the monoaminergic targets to obtain drugs with the properties cited above. It is known that the addition of a 3,4-methylenedioxy group or substitutions on the phenyl ring, especially in para-position, of methcathinone generally shifts selectivity toward SERT and even can behave as partial 5-HT releasers (127,128,(140)(141)(142)(143)(144)(145). For example, it has been reported that trifluoromethyl-substitution of methcathinone in the paraposition dramatically shifts the selectivity of methcathinone toward SERT (146), becoming a SERT-selective partial releaser.…”
Section: Cathinonesmentioning
confidence: 99%